An Investigation of the Absolute Proper Motions of the SCUSS Catalog. (4th January 2016) - Peng, Xiyan; Qi, Zhaoxiang; Wu, Zhenyu; Ma, Jun; Du, Cuihua; Zhou, Xu; Yu, Yong; Tang, Zhenghong; Jiang, Zhaoji; Zou, Hu; Fan, Zhou; Fan, Xiaohui; et al.
Abstract: Absolute proper motions for ∼7.7 million objects were derived based on data from the South Galactic Cap u -band Sky Survey (SCUSS) and astrometric data derived from uncompressed Digitized Sky Surveys that the Space Telescope Science Institute (STScI) created from the Palomar and UK Schmidt survey plates. We put a great deal of effort into correcting the position-, magnitude-, and color-dependent systematic errors in the derived absolute proper motions. The spectroscopically confirmed quasars were used to test the internal systematic and random error of the proper motions. The systematic errors of the overall proper motions in the SCUSS catalog are estimated as -0.08 and -0.06 mas/yr for μα  cos δ and μδ, respectively. The random errors of the proper motions in the SCUSS catalog are estimated independently as 4.2 and 4.4 mas/yr for μα  cos δ and μδ . There are no obvious position-, magnitude-, and color-dependent systematic errors of the SCUSS proper motions. The random error of the proper motions goes up with the magnitude from about 3 mas/yr at u  = 18.0 mag to about 7 mas/yr at u  = 22.0 mag. The proper motions of stars in SCUSS catalog are compared with those in the SDSS catalog, and they are highly consistent.